Quality of life in patients with chronic liver disease - Popović, Dusan Dj; Kisć-Tepavčević, Darija; Kovačević, Nada; Alempijević, Tamara; Krstić, Miodrag; Ranković, Ivan; Martinov, Jelena; Glišić, Tijana; Ješić, Rada; Pekmezović, Tatjana (Vojnosanitetski pregled, 2020)
Background/Aim. Quality of life is impaired in patients with the chronic liver disease (CLD). Patients with this disease have numerous disabling problems which lead to a reduced health related quality of life (HRQoL). The aim of our study was to evaluate the predictive value of selected socio-demographic and clinical characteristics on HRQoL in Serbian cohort of patients with the CLD. Methods. Over a period of one year, we performed a study which included patients with the CLD. We used Short Form Health Survay-36 (SF-36) for assessment of HRQoL. The assessment of depression and anxiety was made by using Hamilton scale of depression and anxiety, while the assessment of fatigue was performed by Fatigue severity scale. Results. The study included 103 patients with the CLD. The average values of the overall SF-36 scores were 52.6 ± 20.4, while the mean score of the composite scores were 53.5 ± 19.6 for the Mental component summary and 49.8 ± 21.3 for the Physical component summary. Some domains of HRQoL were significantly affected by following factors: gender, age, employment status, alcohol consumption, depression, anxiety and fatigue. Predictors of physical components of HRQoL were employment, depression and fatigue, and predictors of mental components were depression and fatigue. Conclusion. The tested socio-demographic, clinical and behavioral factors have an impact on the HRQoL in patients with the CLD. The most important predictors of HRQoL are behavioral factors suggesting the need for an adequate therapeutic action in order to improve the HRQoL in these patients.
Keywords: liver diseases; hepatic insufficiency; quality of life; serbia; sociological factors; demography; depression; surveys and questionnaires.